Abundance and Diversity of Diatom Class Bacillariophyceae in the Waters of Tanjung Luar Fish Landing Based - Niswatul Audah; Lalu Japa; M. Yamin (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2021)
Diatom class Bacillariophyceae are world wide distribution and commonly dominated the phytoplankton community. The community of diatom class Bacillariophyceae of the waters Tanjung Luar Fish Landing Based (FLB) has never been reported. This study aims to determine the abundance and diversity of diatom class Bacillariophyceae. The sampling sites were determined by using a systematic random sampling method. Data of diatom class Bacillariophyceae were analyzed for species abundance, species diversity index and species dominance index calculations. The results showed, that the abundance of diatom class Bacillariophyceae species were 322.000 ind/L (low category), the species diversity index of diatom class Bacillariophyceae was 2.162 (moderate category), and the species dominance index was 0.138 (none of species dominance).